Morphological divergences as drivers of diet segregation between two sympatric species of Serrapinnus (Characidae: Cheirodontinae) in macrophyte stands in a neotropical floodplain lake - Kliemann, Bruna Caroline Kotz [UNESP]; Galdioli, Eliana Maria; Bialetzki, Andréa; Delariva, Rosilene Luciana (FapUNIFESP (SciELO), 2021)
Diet and morphology of Serrapinnus notomelas and Serrapinnus sp.1 were investigated across ontogeny, as a way to elucidate the key elements linked to the resource partitioning (a main driver for species coexistence). Fish sampling was conducted monthly between October 2010 and March 2012. Individuals were captured, identified, and classified into juvenile or adult. Our results show ontogenetic and interspecific differences in feeding abilities and morphological traits. Differences in body shape (relative area of the dorsal fin, length of head, height of the caudal peduncle, the aspect ratio of the pectoral and pelvic fin) favored divergent swimming performances (more maneuverability in S. notomelas and continuous swimming to Serrapinnus sp.1). We also observed divergences in trophic apparatus traits and correlations with different diets. In this context, it is highlighted that understanding the relationship between morphology and diet can assist in elucidating the processes that permeate the coexistence between sympatric species, and between ontogenetic periods. Besides, the relevant contribution of the measures of the trophic apparatus (gill raker length, the number of teeth cuspids, and intestinal coefficient) in trophic segregation seems to be a strong evidence in favor of the proposed discriminatory and predictive capacities of these traits.
Keywords: Diet; Ecomorphology; Interspecific variability; Ontogeny; Trophic apparatus